Kane and Abel - Archer, Jeffrey, 1940- (London : Harper Collins Publishers, 1993)
William Lowell Kane, the son of a Boston millionaire, and Abel Rosnovski, a penniless Polish immigrant, were born on the same day on the opposite sides of the world. The paths of the two men were destined to cross in their ruthless struggle to build a fortune. Rewritten by the author on the 30th anniversary of its first publication.
"First published in hardback on September 1, 1979, in Great Britain by Hodder & Stoughton Limited"--T.p. verso.
Keywords: Capitalists and financiers -- United States -- Fiction; Hotelkeepers -- Fiction; Peasants -- Poland -- Fiction